Penggunaan Media Slide Powerpoint dalam Meningkatkan Prestasi Belajar Siswa Sekolah Dasar Pada Pembelajaran Tematik - A. Jauhar Fuad; Ananda Dwi Permatasari (eL Bidayah: Journal of Islamic Elementary Education, 2019)
The purpose of this study was to improve the quality of learning and learning achievement of grade IV students in my Heroes' Theme using PowerPoint slide media. This research was conducted in two cycles. Where in each cycle has stages that start from doing planning, action, observation and reflection. The results of the study: (1) through the application of PowerPoint slide media can improve the quality of learning; (2) the use of PowerPoint slide media can improve learning achievement 'pahlawanku' Theme in grade IV of SDN Sanan 1. The average value of the class before being subjected to action is 62, in cycle 1 it increases to 71 and in cycle II to 80. The number of students completing study at pre-action as many as 5 students or equal to 35.7%, in the first cycle increased to 9 students or equal to 64.3%, and in the second cycle to 12 students or by 85.7%. The advice given is that the teacher should use innovative models and varied media in learning.